2016
DOI: 10.1038/srep25997
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression profiling on individual breast cancer patients identifies novel panel of circulating microRNA for early detection

Abstract: Breast cancer (BC) is the most common cancer type and the second cause of cancer-related death among women. Therefore, better understanding of breast cancer tumor biology and the identification of novel biomarkers is essential for the early diagnosis and for better disease stratification and management choices. Herein we developed a novel approach which relies on the isolation of circulating microRNAs through an enrichment step using speed-vacuum concentration which resulted in 5-fold increase in microRNA abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 30 publications
5
101
0
Order By: Relevance
“…Indeed, some miRNAs that have been previously linked to carcinogenesis of different organs and tissues, such as miR-2861 [47, 48], miR-4530 [49], miR-638 [50], miR-371b-5p [51], miR-1225-5p [52, 53], miR-296-5p [54, 55], miR-4787-5p [56], miR-4281 [57], miR-4455 [58], miR-197-3p [59], miR-369-5p [60, 61] and miR-505-3p [62] which were found to be altered in brucellosis in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some miRNAs that have been previously linked to carcinogenesis of different organs and tissues, such as miR-2861 [47, 48], miR-4530 [49], miR-638 [50], miR-371b-5p [51], miR-1225-5p [52, 53], miR-296-5p [54, 55], miR-4787-5p [56], miR-4281 [57], miR-4455 [58], miR-197-3p [59], miR-369-5p [60, 61] and miR-505-3p [62] which were found to be altered in brucellosis in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that miR-4270 is down-regulated in stage IV of breast cancer than other early stages, while another study presented evidence that miR-4270 is considered to involve in the malignant ascites in gastric cancer (Tokuhisa et al 2015;Hamam et al 2016). Furthermore, miR-4270 was validated to modulate antigen presentation activity of macrophages by targeting CD300E during helicobacter pylori infection (Pagliari et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, miR 1202, 1207-5p, 1225-5p, and 4270, were found circulating in the blood of breast cancer patients [59]. In human bladder cancer tissue samples, miR 320c was significantly downregulated [60].…”
Section: Exosomesmentioning
confidence: 99%